2016
DOI: 10.1016/j.riem.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Gestión académica de los ciclos clínicos: relaciones y tensiones entre la universidad y el hospital

Abstract: Introducción: La relación entre las escuelas de medicina que dependen de las universidades y las sedes donde los estudiantes de pregrado realizan sus prácticas clínicas vinculan a las instituciones educativas con los centros de atención a la salud que forman parte del Sistema Nacional de Salud. Objetivo: Se analizaron las relaciones y las tensiones en las relaciones de los sujetos posicionados de la educación clínica a partir de las transformaciones introducidas por el Plan de Estudios 2010 de la Faculta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Management is the determining factor in the quality of the performance of the entities. It affects the administrative organization, leadership techniques, and especially the management (Hamui Sutton et al, 2016) on how to use didactic resources; it is a matter of the academic units, the effectiveness of performance that has drawn the continuous attention of school authorities, whose management is oriented in the improvement of educational processes, (Bolaño García, 2019;Villalobo Ropain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Management is the determining factor in the quality of the performance of the entities. It affects the administrative organization, leadership techniques, and especially the management (Hamui Sutton et al, 2016) on how to use didactic resources; it is a matter of the academic units, the effectiveness of performance that has drawn the continuous attention of school authorities, whose management is oriented in the improvement of educational processes, (Bolaño García, 2019;Villalobo Ropain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2012, an interdisciplinary group of experts in medical education (MEDAPROC) at the Medicine School (MS) of the Universidad Nacional Autónoma de México (UNAM) has been working on operationalizing the CBE. In recent research [ 11 ] it was found that both teachers and students had difficulties to understand, implement and assess competencies in day to day educational activities.…”
Section: Introductionmentioning
confidence: 99%